THE APPLICATION OF STUDENT TEAMS ACHIEVEMENT DEVISIONS LEARNING METHOD TO INCREASE MOTIVATION TO LEARN FIQH - Khalilullah, Hijaz; Mardhiah, Ainal (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Education is a process that facilitates students in developing their potential through learning. However, learning success largely depends on student motivation. Observations in class XI IPA 1 at MAS Ruhul Islam Anak Bangsa, Aceh Besar, revealed low student engagement during Fiqh lessons, mainly due to the monotonous lecture method used by the teacher. This study aims to explore the planning, implementation, and effectiveness of the Student Teams Achievement Division (STAD) method in improving students' motivation in learning Fiqh. This research employs Classroom Action Research (CAR) with a purposive sample of 22 students from class XI IPA 1 in the 2025/2026 academic year. Data collection methods included observation, documentation, and questionnaires, analysed through the stages of planning, implementation, and reflection. The findings show that the STAD method significantly increased students' motivation. Students demonstrated improved activeness, responsibility, and comprehension, especially in the topics of inheritance and wills. Group collaboration and interactive discussion encouraged student participation and interest. Questionnaire results indicated a predominantly positive response from students. The use of appropriate learning tools and media further enhanced the effectiveness and enjoyment of the learning process